Students' Perceptions of Using ChatGPT in English Learning at SMA Negeri 5 Pematangsiantar - Tampubolon, Sintia Enrika; Munthe, Melda Veby Ristella; Situmeang, Siska Anggita (Innovative: Journal Of Social Science Research, 2025)
This research aims to determine the students' perceptions of using ChatGPT in English learning at SMA Negeri 5 Pematangsiantar. This research used a qualitative descriptive method. The population of this study consisted of class XI students, with a total of 36 participants selected through purposive sampling. The data were collected using a questionnaire and interview. The results of this study show that out of a total of 720 responses, 170 (22.28%) selected "strongly agree," 470 (61.60%) selected "agree," 99 (12.97%) selected "disagree," and only 24 (3.14%) selected "strongly disagree." This indicates that approximately 83.88% of the overall student responses toward using ChatGPT in English learning were positive. These findings strengthen the conclusion that ChatGPT serves as an effective learning aid for improving students' English skills at SMA